The Role of Islamic Law in Addressing Global Warming: Perspectives from Indonesia and Global Contexts - Islamy, Mohammad Rindu Fajar; Suprima, Suprima; Hermawan, Wawan; Budiyanti, Nurti; Parhan, Muhamad; Logayah, Dina Siti (Mazahib, 2025)
This study examines the role of Islamic law in addressing global warming, focusing on case studies from Indonesia and Western contexts. As emphasized by Indian scholar Mukherjee A, climate change has emerged as an escalating global threat driven primarily by human actions such as excessive fossil fuel consumption, deforestation for industrialization and urbanization, and rapid population growth. These activities accelerate global warming and permanently disrupt ecosystems, leading to significant human suffering. Within Islamic jurisprudence, the principle of Fiqh al-Bī’ah (Islamic environmental jurisprudence) provides both a moral and legal foundation for maintaining ecological balance. Classical Muslim scholars emphasize stewardship (khilāfah) and accountability (mas’ūliyyah) as ethical imperatives guiding human responsibility toward nature. In the contemporary context, Islamic law extends these principles through maqāṣid al-sharī‘ah, particularly the preservation of life (ḥifẓ al-nafs) and nature (ḥifẓ al-bi’ah), which demand sustainable and responsible engagement with the environment. This research employs a Systematic Literature Review (SLR) alongside an analysis of classical Islamic works, examining 578 scholarly papers to ensure comprehensive coverage. The Miles and Huberman framework, comprising data reduction, data display, and conclusion drawing, was applied to guide the data analysis. The findings reveal that Islamic law offers both normative and practical mechanisms for mitigating climate change: (1) strengthening Fiqh al-Bī’ah as a legal-ethical response, (2) promoting ecological citizenship within Society 5.0, (3) enforcing robust environmental regulations and local capacity building, and (4) integrating technological innovation with sustainable practices. The study concludes that Islamic law provides a holistic ethical and legal foundation for environmental stewardship, harmonizing traditional jurisprudence with modern sustainability initiatives to address global warming both globally and locally.